The Differential Effects of Mindfulness and Distraction on Affect and Body Satisfaction Following Food Consumption - Tsai, Alice; Hughes, Elizabeth K.; Fuller-Tyszkiewicz, Matthew; Buck, Kimberly; Krug, Isabel (Frontiers in Psychology, 2017)
This study investigated whether engaging in mindfulness following food consumption produced changes in affect and body satisfaction, as compared to a control distraction task. The moderating effects of eating pathology and neuroticism were also examined. A total of 110 female university students consumed food and water before engaging in either a mindfulness induction or a control distraction task. Participants completed trait measures of eating pathology and neuroticism at baseline, and measures of state affect and body satisfaction before and after food consumption, and after the induction. Results revealed that consuming food and water reduced positive affect. Unexpectedly, both the mindfulness group and distraction control group experienced similar improvements in negative affect and body satisfaction following the induction. Eating pathology and neuroticism did not moderate the observed changes. These findings suggest that both mindfulness and distraction may contribute to the effectiveness of treatments for disordered eating that incorporate both of these techniques, such as Dialectical Behavior Therapy.